Image files from neuronal autoantibody screening for patients undergoing memory impairment investigations - Theorell, Jakob (Karolinska Institutet, 2026)
This dataset contains image files from 1021 memory clinic patients that have undergone screening for 5 different neuronal autoantibodies. The files are in the .nd2 format, owned by Nikon, but can be accessed through multiple open-source platforms, for example ImageJ, BioFormats or RBioFormats. For each individual, there are five files with two duplicates (two for each antigen). Each file contains three images, 2048+2048 pixels in size, that have been taken from random locations in a well in a microscopy-grade 96-well plate. The cells in the images are 293 MSR cells (ThermoFisher). For the full protocol, see https://github.com/jtheorell/Laboratory-protocols.

Detta dataset består av bild-filer i .nd2-format från 1021 patienter under minnesutredning. Bilderna visar på resultatet av screening för de fem vanligaste antikropps-specificiteterna att ge autoimmun encefalit hos äldre. Varje experiment genomfördes (minst) två gånger per prov, vilket betyder att det finns tio filer per individ. varje fil innehåller i sin tur tre bilder från slumpartade platser i samma experimentella brunn. Se https://github.com/jtheorell/Laboratory-protocols för ytterligare detaljer.
Image files from neuronal autoantibody screening for patients undergoing memory impairment investigations
Keywords: Dementia; Demens; DEMENTIA; DEMENS; Autoantibodies; Autoantikroppar; Autoimmune Diseases of the Nervous System; Autoimmuna nervsjukdomar; Dementia due to autoimmune encephalitis; demens orsakad av autoimmun encefalit; Autoimmune limbic encephalitis; autoimmun encefalit i limbiska systemet; Autoimmune encephalopathy; autoimmun encefalit; Specific diseases, disorders and medical conditions; Specifika sjukdomar, störningar och medicinska tillstånd; Neurosciences; Neurovetenskaper; Immunology in the Medical Area; Immunologi inom det medicinska området; Signs and symptoms; pathological conditions; Tecken och symtom; patologiska tillstånd